Implementasi Kewenangan Pemerintah Daerah Terhadap Jalan Rusak - Sawelet, Agnes; Nirahua, Salmon Eliazer Marthen; Saija, Vica Jillyan Edsti (Faculty of Law, Universitas Pattimura, 2022)
Introduction: This study discusses the authority of the local government on damaged roads in Taniwel District, West Seram Regency, Maluku Province.Purposes of the Research: Reviewing and Analyzing the Authority of the Western Seram Government on Damaged Roads in Taniwel District and Reviewing and Analyzing the Non-Performance of Maintenance of Damaged Roads by the Western Seram Government as an Abuse of Authority. Methods of the Research: The research used is a legal research method that uses empirical facts and descriptive type taken from human behavior, both verbal behavior obtained through interviews and real behavior carried out through direct observation Data and information collected from research results, both interviews with relevant agencies or from the village government which is then analyzed through a qualitative approach, namely an analytical descriptive method by using a way of grouping and selecting the data obtained from research to obtain conclusions.Results of the Research: Damaged roads in Buria Village, Taniwel District, West Seram Regency (SBB) are categorized as Regency roads and are the authority of the West Seram Regency (SBB) Regional Government, based on Law Number 23 of 2014 concerning the division of road affairs, including the area of provincial roads. , district, city and based on the results of research that the author did. The West Seram Regency Government (SBB) cannot carry out road maintenance in Buria Village, Taniwel District, West Seram Regency because there are various obstacles faced so that the road maintenance process cannot be carried out from 2018 to 2021, based on Articles 17 and 18, it is not The maintenance of roads by the West Seram Regency Government (SBB) on damaged roads cannot be categorized as an abuse of authority but is an oversight of the Regional Government because the Regional Government has allowed the road to be damaged until now.